ОСВІТНІЙ ПОТЕНЦІАЛ CHATGPT ОЧИМА СТУДЕНТІВ: УКРАЇНСЬКИЙ ВИМІР ВИКОРИСТАННЯ ГЕНЕРАТИВНОГО ШТУЧНОГО ІНТЕЛЕКТУ - ushlyak, Marina; Semenikhina, Olena (Information technologies and learning tools, 2025)
Стрімкий розвиток генеративного штучного інтелекту (ШІ), зокрема ChatGPT, актуалізує потребу осмислення його освітнього потенціалу та ризиків. Викладачі і студенти сучасних університетів одночасно виступають активними користувачами й критиками технологій ШІ, що породжує суспільні й академічні дискусії щодо їхньої користі, надійності та етичних обмежень. Мета статті – дослідити уявлення студентів українських закладів вищої освіти про ChatGPT та практики його використання як освітнього інструмента. Емпірична база ґрунтується на відповідях 379 респондентів різних освітніх рівнів і спеціальностей, отриманих у межах міжнародного опитування. Для аналізу застосовано описову статистику, кластеризацію, t-тест, дисперсійний та кореляційний аналіз. Оригінальність дослідження полягає в першому для українського дискурсу емпіричному виокремленні трьох типів користувачів ChatGPT на основі кластерного аналізу: високоактивні, помірно активні та низькоактивні (скептики). Ця типологія розкриває диференційованість цифрової автономії студентів та їх готовність до інтеграції ШІ. Важливим науковим результатом є також відсутність статистично значущих відмінностей у ставленні до ChatGPT залежно від статі та освітнього рівня, що свідчить про універсальність його сприйняття українською студентською молоддю. Натомість виявлено позитивні кореляції між частотою й досвідом використання та загальною оцінкою функціональності ChatGPT. Результати показали, що ChatGPT використовується студентами переважно з навчальною метою, однак нерегулярно та з помірним рівнем довіри. Найвищі оцінки отримали когнітивно орієнтовані функції інструмента – спрощення складної інформації, узагальнення великих обсягів даних, ефективна подача матеріалу. Водночас низькою залишається довіра до здатності ChatGPT забезпечувати достовірність результатів. Запропоновано рекомендації щодо диференційованого впровадження ChatGPT в освітній процес з урахуванням рівня цифрової зрілості здобувачів освіти. Підкреслено необхідність формування ШІ-грамотності для підтримки академічної доброчесності й розвитку ключових компетентностей XXI століття. The rapid development of generative artificial intelligence (AI), particularly ChatGPT, highlights the need to consider both its educational potential and its risks. University educators and students today act simultaneously as active users and as critics of AI. This dual role generates public and academic debates about their usefulness, reliability, and ethical constraints. The purpose of this paper is to examine the perceptions of Ukrainian higher education students regarding ChatGPT and their practices of using it as an educational tool. The empirical basis comprises responses from 379 participants representing diverse educational levels and fields of study. The data were collected as part of an international survey. The analysis applied descriptive statistics, clustering, t-tests, analysis of variance, and correlation analysis. The originality of this research lies in being the first empirical attempt, in the Ukrainian context, to identify three types of ChatGPT users through cluster analysis: highly active, moderately active, and low-active (skeptical). This typology demonstrates the diversity of students’ digital autonomy and their readiness to integrate AI into learning. An important scientific finding is the absence of statistically significant differences in attitudes toward ChatGPT by gender or educational level. This indicates the universality of its perception among Ukrainian students. At the same time, positive correlations were found between frequency and experience of use and the overall evaluation of ChatGPT’s functionality. The results show that students mostly use ChatGPT for educational purposes. However, their use is irregular and accompanied by only moderate levels of trust. The highest ratings were given to cognitively oriented functions such as simplifying complex information, summarizing large volumes of data, and presenting material effectively. By contrast, trust remains low regarding ChatGPT’s ability to ensure the accuracy of results. The paper provides recommendations for the differentiated implementation of ChatGPT in the educational process, considering students' varying levels of digital maturity. It also emphasizes the need to develop AI literacy to support academic integrity and to foster key competencies for the 21st century.